2019
DOI: 10.3389/fphys.2019.00620
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction Increases Cardiovascular Risk in the Presence of Sleep Apnea

Abstract: The high prevalence of sleep apnea syndrome (SAS) and its direct relationship with an augmented risk of cardiovascular disease (CVD) have raised SAS as a primary public health problem. For this reason, extensive research aiming to understand the interaction between both conditions has been conducted. The advances in non-invasive autonomic nervous system (ANS) monitoring through heart rate variability (HRV) analysis have revealed an increased sympathetic dominance in subjects suffering from SAS when compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…Moreover, these differences in the CPC parameters are more evident during sleep than right before the SBT, what could be due to the loop gain. In other words, patients with failed weaning may be experiencing more apnoea events at night, which is directly related to a reduced RSA and higher cardiovascular risk 31 , 56 . In fact, the parasympathetic activity is well known to be predominant during sleep at night and, consequently, it is in this moment when the CPC mechanism is stronger.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these differences in the CPC parameters are more evident during sleep than right before the SBT, what could be due to the loop gain. In other words, patients with failed weaning may be experiencing more apnoea events at night, which is directly related to a reduced RSA and higher cardiovascular risk 31 , 56 . In fact, the parasympathetic activity is well known to be predominant during sleep at night and, consequently, it is in this moment when the CPC mechanism is stronger.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory dysfunction can influence cardiovascular health, and cardiovascular diseases are often associated with respiratory diseases ( Garcia et al, 2013 ). Breathing disorders and pulmonary diseases are tightly linked to autonomic dysfunction ( van Gestel and Steier, 2010 ; Milagro et al, 2019 ). On the other hand, it has been demonstrated that the maintenance of correct cardiorespiratory coupling exerts beneficial cardiovascular effects in patients with an attenuated RSA ( Ben-Tal et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these differences in the CPC parameters are more evident during sleep than right before the SBT, what could be due to the loop gain. In other words, patients with failed weaning might be experiencing more apnoea events during the night, which is directly related to a reduced RSA and a higher cardiovascular risk 40,67 . In fact, the PNS activity is well known to be predominant during sleep at night.…”
Section: Discussionmentioning
confidence: 99%